261 Staging of high-risk endometrial cancer with PET/CT and sentinel lymph node mapping algorithm. (18th September 2019) - Buda, A; Crivellaro, C; Guerra, L; De Bernardi, E; Di Martino, G; Paderno, M; Dell'Orto, F; Grassi, T; Magni, S; Di Meo, ML
Abstract : Objectives: We evaluated the role of PET/CT and sentinel lymph node (SLN) biopsy in women with early stage high-risk endometrial cancer (G2 and deep myometrial invasion, G3, serous, clear cell carcinoma or carcinosarcoma). Methods: Between November 2006 to June 2018, 116 women underwent PET/CT scan followed by surgery were included. Fitty-one percent (60/116) patients underwent full lymphadenectomy (Group A). Forty-eight percent of patients (56/116) underwent SLN mapping with ultrastaging (Group B). Histological findings were used as the reference standard. Results: Patients with positive node were 11 (18.3%) and 14 (25%) in group A and B, respectively. In group A, 10 were correctly identified by PET/CT, with only 1 FN case. Sensitivity, specificity, accuracy, positive-predictive value-PPV and negative predictive value-NPV of PET/CT for pelvic LN metastases resulted 90.1%, 98%, 96.7%, 90.1%, 98%, respectively. In group B, 4 were correctly identified by PET/CT, while 10 cases resulted falsely negative. Sensitivity, specificity, accuracy, PPV, and NPV of PET/CT for pelvic LN metastases were 28.5%, 97.7%, 80.4%, 80%, 80.3%, respectively. In 5 of 10 FN PET, micrometastases, and/or ITC were detected by SLN ultrastaging. Overall, sensitivity, specificity, accuracy, PPV, and NPV of PET/CT resulted 56%, 97.8%, 88.7%, 87.5%, 89%, respectively. Conclusions: PET/CT demonstrated high specificity in detecting pelvic LN metastases and its high PPV can be useful to refer patients to appropriate debulking surgery. Ultrastaging of SLN increased the identification of metastases (18.3%-25%) not detectable by PET/CT because of its spatial resolution, increasing false-negative PET/CT findings. The combination of both modalities seems promising for nodal staging purpose.